The native energy "After its expresion": The "Process" of José Carlos Mariátegui - Cervera Salinas, Vicente (2011)
Starting from a proposal of Pedro Henríquez Ureña, about the cultural process in Hispanic America, the authors seek to relate the Dominican intellectual postulates from the propositions of Jose Carlos Mariategui, that are framed in a dialectical process of affirmation and denial, of continuity and change, as it happen with modernism on the romanticism or the tendencies of vanguard against modernism.